(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
This research reports on the performance of two re-sampling methods (Bootstrap and Jackknife) relationship and significance of social-economic factors (age, gender, marital status and settlement) and modes of HIV/AIDS transmission to the HIV/AIDS spread. Logistic regression model, a form of probabilistic function for binary response was used to relate social-economic factors (age, sex, marital status and settlement) to HIV/AIDS spread. The statistical predictive model was used to project the likelihood response of HIV/AIDS spread with a larger population using 10,000 Bootstrap re-sampled observations and Jackknife re-sampled. From the analysis obtained from the two re-sampling methods, we can conclude that HIV transmission in Kebbi state is higher among the married couples than single individuals and concentrate more in the rural areas.